Genomic characterization of plasmids of mcr-1-positive Escherichia coli isolated from cohabiting rats, dairy cattle and pigs - Dominguez, Johanna Elizabeth; Martino, Florencia; Lovera, Rosario; Casanova, Natalia Andrea; Seah, Christine; Cavia, Regino; Corso, Alejandra; Melano, Roberto G.; Faccone, Diego; Fernandez Miyakawa, Mariano Enrique (BioMed Central, 2025)
Background: Antimicrobial resistance has become a significant global issue impacting humans, animals, and the environment. Currently, the focus of concern has shifted to the environment, which can act as a reservoir and significantly contribute to the spread of resistance genes. This study aimed to elucidate the potential transmission of mcr-1, which confers colistin resistance, among Escherichia coli isolates from pigs, dairy cattle, and co-habiting rodents. In March 2018, 30 fecal samples were collected from three pig farms and one mixed cattle farm, and 31 cecal contents from rats (Rattus norvegicus) captured from the same four animal farms were analyzed. Results: Out of 26 mcr-1 positive E. coli isolates, 16 came from six rats, 10 from four pigs, and none from dairy cattle. The mcr-1-positive isolates from cohabiting rats and pigs were genetically unrelated, based on different XbaI-PFGE profiles. The plasmid profiles of one isolate per animal from each farm were analyzed by S1-PFGE. E. coli isolates from cohabiting rats and pigs showed plasmid bands of similar sizes (33 or 65 kb). To investigate the horizontal transfer of these plasmids between the animals, two pairs of E. coli isolates from pig farms 1 and 3 were selected for WGS analysis. Three of the isolates (EcoP3-1, EcoC2-1 from pigs, and Eco1266-6 from a rat) belonged to clonal complex 10 (CC10), while the other rat isolate (Eco1284-6) belonged to CC398 (ST398). Eco1266-6 (rat) and EcoC2-1 (pig) from cohabiting animals in pig farm 1 carried IncX4 plasmids with the mcr-1.1 variant. The plasmid sequences were almost identical (99.98% identity), both carrying the mcr-1.1/pap2 segment. pEcoC2-1 had a complete ISVsa5 insertion sequence upstream of the mcr-1 gene. Eco1284-6 (rat) and EcoP3-1 (pig) from pig farm 3 carried IncI2 plasmids with different allelic variants of mcr-1 (mcr-1.5 and mcr-1.1). Conclusions: E. coli isolates from cohabiting rats and pigs were genetically distinct, but one pair of isolates had very similar IncX4 plasmids, suggesting the potential for horizontal spread of plasmids carrying mcr genes. These findings suggest a threat of resistant E. coli spreading between cohabiting animals and into the environment. This underscores the importance of conducting integrated One-Health studies.